2009
DOI: 10.1186/1743-8462-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Medication safety in acute care in Australia: where are we now? Part 1: a review of the extent and causes of medication problems 2002–2008

Abstract: Background: This paper presents Part 1 of a two-part literature review examining medication safety in the Australian acute care setting. This review was undertaken for the Australian Commission on Safety and Quality in Health Care to update a previous national report on medication safety conducted in 2002. This first part of the review examines the extent and causes of medication incidents and adverse drug events in acute care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
178
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(187 citation statements)
references
References 41 publications
3
178
0
6
Order By: Relevance
“…2 Roughead and Lexchin estimated that 2 million Australians experience an ADE annually, of which half are moderate or severe with 138 000 requiring hospitalisation. 3 Further, a recent review by Roughead and Semple 4 concluded that 2-3% of Australian hospital admissions are medication related, representing an estimated 190 000 medication-related hospital admissions per year, with associated costs of A$660 million. Studies by Galbraith 5 and Dartnell et al 6 indicate that unplanned admissions via the Emergency Department (ED) are even more likely to be medication related, with the authors reporting that ADEs account for 6.4% and 5.7% of admissions, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Roughead and Lexchin estimated that 2 million Australians experience an ADE annually, of which half are moderate or severe with 138 000 requiring hospitalisation. 3 Further, a recent review by Roughead and Semple 4 concluded that 2-3% of Australian hospital admissions are medication related, representing an estimated 190 000 medication-related hospital admissions per year, with associated costs of A$660 million. Studies by Galbraith 5 and Dartnell et al 6 indicate that unplanned admissions via the Emergency Department (ED) are even more likely to be medication related, with the authors reporting that ADEs account for 6.4% and 5.7% of admissions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a 2009 report by the National Prescribing Service concluded that approximately 5.6% of general hospital admissions and 30.4% of hospital admissions in patients 75 years and older in Australia are related to ADEs. 7 Of the Australian studies that have assessed preventability, Roughead and Semple 4 found that approximately 50% of ADE-related admissions (ADE-RAs) were potentially preventable.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian di Australia didapatkan 190.000 pasien di rawat inap berkaitan dengan medication error per tahun dan menghabiskan biaya 660 juta dolar (Roughead and Semple, 2009).…”
Section: Pendahuluanunclassified
“…17 Researchers claim that several factors may predispose to medication errors, such as overwork, lack of attention during medication prescribing, dispensing and administering processes, communication failures between teams and between sectors, lack of information about the patient, difficulty in accessing information about medications, as well as environmental and individual factors. 18 Incorporating principles to reduce human error by minimizing memory lapses, promoting access to drug information, and developing internal training standards reduces the likelihood of failures and increases the chance of intercepting them before resulting in harm to the patient. In this sense, strategies such as the standardization of processes, the use of information technology resources, permanent education and, above all, the monitoring of professional practices in all stages of the process involving the medicine must be included.…”
mentioning
confidence: 99%